Accuracy of the LPM tracking system considering dynamic position changes - Ogris, G.; Leser, R.; Horsak, B.; Kornfeind, P.; Heller, M.; Baca, A. (Journal of Sports Sciences, 2012)
This study investigates the accuracy of the tracking system LPM (Local Position Measurement). The goal was to determine detailed error values of the system in the context of sports performance analyses. Six moderately trained male soccer players (amateur level) performed 276 runs on three different courses at six different speeds. Additionally, ten small-sided game plays were carried out. All runs and game plays were recorded with the LPM tracking system and the motion capture system VICON simultaneously. VICON served as the reference system. The absolute error of all LPM position estimations was on average 23.4±20.7 cm. The estimation for average velocities varied between 0.01 km/h and 0.23 km/h, the maximum speed estimations differed by up to 2.71 km/h. In addition, the results showed that the accuracy of the LPM system is highly dependent on the instantaneous dynamics of the player and decreases in the margins of the observation field. These dependencies were quantified. Considering commonly used applications of position tracking systems in sports (Leser, Ogris, & Baca, 2011), the accuracy of LPM is acceptable for position and velocity estimations. The system provides valuable results for average velocities but seems to be far less reliable when dealing with high dynamic movements and measuring instantaneous velocities.